(untitled) (The Review of Diabetic Studies, 2025)
Background: Healthcare organizations, especially in nursing, face increasing challenges due to evolving patient needs, resource constraints, and crises like the COVID-19 pandemic. Transformational leadership is seen as a crucial factor in enhancing resilience and adaptive capacity within healthcare organizations, particularly nursing leadership. However, there is limited research on how transformational leadership influences resilience in nursing teams, especially in dynamic and high-stress environments. Aim: This systematic review aims to assess the impact of transformational leadership on the adaptive capacity and resilience of healthcare organizations, focusing on nursing leadership. The review seeks to understand how leadership behaviors influence nurse resilience, job satisfaction, and organizational outcomes, especially during times of crisis and change. Method: A comprehensive search was conducted across five major databases (PubMed, Scopus, Web of Science, CINAHL, and Google Scholar) to identify studies published between 2021 and 2025. Ten primary studies were selected for inclusion based on their focus on transformational leadership in nursing and its relationship with resilience and adaptive capacity. Results: The review found that transformational leadership behaviors, including idealized influence, inspirational motivation, and individualized consideration, positively impacted nurse resilience, job satisfaction, and retention. Leaders who demonstrated these behaviors fostered a supportive and adaptable work environment, which enhanced organizational resilience, particularly during crises. Conclusion: Transformational leadership plays a pivotal role in enhancing resilience and adaptive capacity in healthcare organizations. The findings suggest that developing transformational leadership competencies in nurse leaders is essential for promoting nurse well-being, improving job satisfaction, and ensuring a more resilient healthcare workforce.